2018
DOI: 10.1002/chem.201802902
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Sulphur‐ and Nitrogen‐Containing Porous Polymers with Tuneable Donor–Acceptor Domains for Light‐Driven Hydrogen Evolution

Abstract: Light-driven water splitting is a potential source of abundant, clean energy, yet efficient charge-separation and size and position of the bandgap in heterogeneous photocatalysts are challenging to predict and design. Synthetic attempts to tune the bandgap of polymer photocatalysts classically rely on variations of the sizes of their π-conjugated domains. However, only donor-acceptor dyads hold the key to prevent undesired electron-hole recombination within the catalyst via efficient charge separation. Buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 50 publications
3
23
0
Order By: Relevance
“…For the spectra shown in Figure e, it is easily observed that these polymers have different PL lifetimes and the estimated average lifetimes ( τ avg ) increased in order of FSO‐FS z , FSO‐BP, FSO‐F, and FSO‐FS. This tendency is accordance with the decrease of E b , suggesting that the high charge mobility in these polymers is due to the lower energy loss of E CT .…”
Section: Methodssupporting
confidence: 83%
“…For the spectra shown in Figure e, it is easily observed that these polymers have different PL lifetimes and the estimated average lifetimes ( τ avg ) increased in order of FSO‐FS z , FSO‐BP, FSO‐F, and FSO‐FS. This tendency is accordance with the decrease of E b , suggesting that the high charge mobility in these polymers is due to the lower energy loss of E CT .…”
Section: Methodssupporting
confidence: 83%
“…Figure S11 shows the room-temperature PL spectra of all of the polymers.A sE b decreases,acorresponding PL quenching is observed, indicating ad ecreased recombination of photogenerated charges. [19] Moreover, the time-resolved PL spectra show the lifetimes of the charges.For the spectra shown in Figure 2e,itis easily observed that these polymers have different PL lifetimes and the estimated average lifetimes (t avg ) increased in order of FSO-FS z ,F SO-BP,F SO-F,a nd FSO-FS.T his tendency is accordance with the decrease of E b ,s uggesting that the high charge mobility in these polymers [20] is due to the lower energy loss of E CT .…”
mentioning
confidence: 67%
“…Exchange of Pt co-catalyst to Pd can even diminish photocatalytic activity of conjugated porous polymers,a sitwas shown in our previous study. [25] In summary, we setout to examinerationaldesignconcepts fore nhancedp hotocatalystsb ased on theh ighly-modular family of sulfur andn itrogen containing porous polymers (SNPs).W edesignedeight SNPs ystems that featureasimilar pore structureyet have arange of opticalbandgapsand come with andw ithout spacersb etween thed onor (aromatic thiophenes)a nd acceptor (triazine) moietiest oe nables trong andw eakc harge-transfere ffects,r espectively. Composition, properties,a nd computationalr ationalization of thesep olymers narrowsd ownt he "GoldilocksZ one" fort he ideal polymerp hotocatalyst as follows: 1) Therei saconceivable rangeo fo ptimal (indirect) band gaps forp hotocatalysis between2 .1 and2 .3 eV that eclipses thep rotonr eduction andthe sacrificialdonor oxidationpotentials.…”
Section: Angewandte Chemiementioning
confidence: 99%